Analysis of the process of translation of knowledge regarding early childhood at the undergraduate level - Pina-Oliveira, Alfredo Almeida; Moreira, Roseli Lana; Pécora, Rosemary Aparecida Fracolli; Chiesa, Anna Maria (Revista da Escola de Enfermagem da USP, 2014)
Objective To analyze innovative contents on Early Child Development Promotion. Method This action-research involves nine faculties from four Higher Education Institutions at inner-state of São Paulo, Brazil.Data were collected by syllabi analyses (2009-2011), interviews and focus group. We have adopted an ECDP underpinning from international consensus, thus evaluating KT Results We have found relevant incorporation between teaching and extension in Nursing (87,5%) and Psychology (75%) undergraduate courses, while Pedagogy was restricted to teaching. Conclusion This KT evaluation has evinced innovative potential of extension, regardless teaching and research, for a better Early Childhood.